Autonomy, Enlightenment, Justice, Peace – and the Precarities of Reasoning Publically - Westphal, Kenneth R. (Conatus - Journal of Philosophy, 2023)
The First World War was supposed to end all wars, though soon followed WWII. Since 1945 wars continued to abound; now we confront a real prospect of a third world war. Many armed struggles and wars arise in attempts to end repressive government; still more are fomented by repressive governments, few of which acknowledge their repressive character. It is historically and culturally naive to suppose that peace is normal, and war an aberration; war, preparations for war and threats of war belong to ‘normal’ human life. Our tolerance, acceptance or fostering of such repeated injustices and atrocities indicate pervasive failures to understand fundamentals of justice, and what we owe morally to ourselves and to all others, together with our responsibilities to preserve the biosphere, not merely our own store(s) of reserves. As matters both of justice and prudence we must re-orient ourselves, individually and collectively, to promote justice, peace and ecological responsibilities by identifying and instituting just forms of social cooperation, domestically and internationally. All of these are our problems, whether we recognize them or continue our pervasive negligence. We urgently require cogent understanding of the social dimensions of human judgment, rational assessment, right action, and public reason. This requires understanding (inter alia) how Kant’s explication of rational judgment and justification is fundamentally social, how these features of rational judgment and justification are constitutive of Kant’s account of individual autonomy, and how they are central to Kant’s account of proper public use of reason. Reasoning publically remains precarious, not because – as often alleged – the ‘Enlightenment project’ has failed. It has not failed, it has been thwarted, and in our public responsibilities we have too often failed it.